2012
DOI: 10.1002/acr.21602
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of the bidirectional association between pain and depressive symptoms in patients with psoriatic arthritis

Abstract: Objective. To test the bidirectional hypothesis that depressive symptoms influence changes in pain over time, and pain influences changes in depressive symptoms. Methods. A total of 394 patients attending the University of Toronto Psoriatic Arthritis clinic were followed over a mean period of 7.5 years with annual assessments, including number of swollen joints (SJC), Health Assessment Questionnaire (HAQ), and the Medical Outcomes Survey Short Form 36 (SF-36). Linear mixed-effects models were used to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 37 publications
4
39
1
2
Order By: Relevance
“…Studies have consistently demonstrated temporal associations between depression and pain among RA, PsA, and EIA patients (12,13,18,20). Research also indicates that depression moderates stress-associated changes in pain, EGA, and TJC, but these associations were not linked to immune activation (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have consistently demonstrated temporal associations between depression and pain among RA, PsA, and EIA patients (12,13,18,20). Research also indicates that depression moderates stress-associated changes in pain, EGA, and TJC, but these associations were not linked to immune activation (19).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of psoriatic (PsA) and early undifferentiated inflammatory arthritis (EIA) patients have demonstrated significant temporal bidirectional effects between depression and disease activity, and possible causal mechanisms include biological, psychological, and behavioral factors, as well as the interaction of these different domains (1113). Cross-sectional research has consistently demonstrated strong positive associations between depression and composite disease activity, pain, function, global assessments, and acute-phase reactants (1417).…”
Section: Introductionmentioning
confidence: 99%
“…We also determined what challenges patients were experiencing in receiving treatment with biologic therapies and found that about one-third of patients with PsA reported 6 The …”
Section: Rheumatologymentioning
confidence: 99%
“…PsA may present with ≥ 1 clinical subtype, including peripheral joint inflammation, enthesitis, dactylitis, axial spondylitis, and varying severity of nail and skin changes; the heterogeneous aspect of this disease makes diagnosis and treatment challenging 4,5 . Some patients with PsA may experience destruction of the joints, and functional and psychosocial impairments are common 6,7,8 . Additionally, PsA is associated with an increased prevalence of comorbidities such as metabolic and cardiovascular disease, further complicating management of the disease 9 .…”
mentioning
confidence: 99%
“…Comorbid psoriasis and psoriatic arthritis increase the risk of depression beyond that of psoriasis alone. Psoriatic arthritis adversely impacts sleep, work, and socialization [4,5].…”
Section: Introductionmentioning
confidence: 99%